ISOLASI DAN KARAKTERISASI SENYAWA METABOLIT SEKUNDER DARI EKSTRAK METANOL AKAR TUMBUHAN TUNJUK LANGIT (Helminthostacshys zeylanica) - novia rahim (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2016)
Helminthostacshyszeylanica is a plant of the family ophioglossaceae known as the tunjuk langit plant. The roots of this plant is used as a 100 days cough remedy, dysentery, nasal disease and lung disease. This plant contains saponins, andflavonoids. This study aims to isolate and characterizethe flavonoid compounds from the root of tunjuk langit. Isolation methods used polar fractionation method. Some 7.5 kg oftunjuk langit wasmacerated with methanol17 L for 3x24 hours later ultrasonicatide for 1 hour. Extract thick about 100 gr then partifioned with methanol mixture and n-hexan 2:1. Methanol fraction of partition result thickened then in chromatography liquid vacuum (VLC) in 12 fraction (n-hexane – etilacetate – methanol). Flavonoid compound obtained after VLC result on fraction 5 and 6 is combined then in flash chromatography. Flavonoid compound such yellow crictal on vial 19 is coded as HZ19. The purity of this compound was analized by TLC and HPLC as well as determination of the melting point range. Structure of pure compound was determined using spectroscopy method including UV-Vis, infrared (IR). Based on spectroscopic data HZ19 known that flavonoid is a Flavon kind in ugonin group.